Critical issues in early childhood teacher education. Volume 2 : international perspectives - Jones, Ithel; Lin, Miranda (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
In recent years there have been significant changes in education across the globe, largely as a result of changing demographics, technological developments, and increased globalization. Relatedly, the changing needs of societies and families, along with new research findings, provide new directions in early childhood education. Consequently, early childhood teachers today are faced with higher and more complex expectations to help ensure that their students achieve their full potential. Such expectations suggest that early childhood teachers should be professionals who are able to draw on a robust knowledge base in making educational decisions. It follows that teacher education programs should develop and implement innovative programs that can potentially enhance the quality of our future teachers.An awareness of pressing issues in the field of early childhood teacher education led the editors to develop this volume. The chapters in these two volumes bring together scholars from across the US and the globe who are interested in improving the quality of early childhood teacher education. The chapters present their experiences, perspectives, and lessons learned as they addressed some of the challenging issues concerning the education and preparation of future early childhood teachers. The various issues and perspectives from different states in the US or countries across the globe provide insights into current issues and dilemmas facing the field. The contributions of these scholars should inform the discourse on early childhood teacher education and help those who work with preservice teachers improve the quality of their work.